Minimally invasive and robot-assisted interventions in the treatment of gynecological malignant tumors: opportunities for preserving reproductive function - A. U. Khamadyanova; T. T. Gaev; D. O. Gatsoev; V. V. Andreev; A. S. Pazhitnova; E. O. Tikhonova; V. G. Kim; D. A. Talalaeva; V. V. Agapova; R. S. Botina; A. K. Yakovleva; S. D. Vasilieva; et al. (Акушерство, гинекология и репродукция)
Aim: to systematize and analyze current data on the use of minimally invasive and robot-assisted interventions in the treatment of gynecologic malignant tumors in reproductive age women who wish to preserve fertility.Materials and Methods. The search was conducted in the PubMed/MEDLINE, Scopus, Web of Science, and eLibrary databases among the primary sources published from 01.01.2000 tо 28.02.2025. There were retrieved keywords and MeSH (Medical Subject Headings) terms including: “robotic surgery”, “robot-assisted surgery”, “fertility preservation”, “gynecologic cancer”, “cervical cancer”, “endometrial cancer”, “ovarian cancer”, “reproductive age”, “minimally invasive surgery”, “uterine transplantation”, as well as the corresponding Russian terms. Original studies focusing on oncologic and reproductive outcomes in women under the age of 45 were included in the analysis. The methodology followed the PRISMA guidelines. The final analysis included 53 publications.Results. The data evidence about the effectiveness and oncologic safety of fertility-preserving approaches in early-stage cervical, endometrial, and ovarian cancer. Robot-assisted interventions vs. conventional techniques demonstrated comparable or superior outcomes in fertility preservation with fewer complications and faster recovery. Additional topics addressed include ovarian transposition, uterine transplantation, and alternative fertility preservation strategies.Conclusion. Robot-assisted surgery extends the potential for fertility-sparing treatment of gynecologic malignant tumors in reproductive age women. Such interventions should be performed in specialized centers by multidisciplinary teams. Further research is needed to standardize treatment protocols and evaluate long-term oncologic and reproductive outcomes.